IMPROVING ADVERTISING TEXT WRITING ABILITIES WITH THE PROJECT BASED LEARNING METHOD ON STUDENTS OF CLASS VIII C OF DWIJENDRA MIDDLE SCHOOL, DENPASAR ACADEMIC YEAR 2024/2025 - Ida Ayu Novita Yogan Dewi; Islachul Amalia (International Conference on Multidisciplinary Research Perspective, 2025)
The development of writing skills, including writing advertising texts, needs serious attention from the most basic level of education, because writing skills are not formed automatically. The low skills of students in writing advertising texts are caused by the lack of interest in reading so that their knowledge and vocabulary are limited and cause students to be less able to express their thoughts through writing. Departing from these problems, researchers try to offer other learning methods to improve students’ abilities in writing advertising texts. One of the learning methods that can stimulate student creativity is the Project Based Learning (PjBL) learning method. PjBL is an innovative method in student-centered learning because the teacher only acts as a motivator and facilitator. The purpose of this study is to determine whether the Project Based Learning (PjBL) learning method can improve the skills of writing advertising texts of class VIII C students of Dwijendra Middle School. Writing is a language skill used to communicate indirectly, not face-to-face, with others (Tarigan, 2013). Advertising text is an important foundation in understanding how persuasive messages can be created and delivered to audiences effectively. The data collection methods used in this study were tests and observations. The type of test used was a student learning outcome test. This study was a Classroom Action Research (CAR). The approach used was a quantitative approach. The research design consisted of planning, observation, implementation, and reflection, which were carried out through two cycles. The data analysis technique used in this study was descriptive statistical analysis, and informal and formal techniques were used to present the results of the data analysis. The results of this study indicate that the average value of the skills of writing advertising texts using the Project Based Learning (PjBL) method of class VIII C students of Dwijendra Middle School, in the pre-cycle was 66.4 and cycle I was 71.8 and in cycle II it became 75.9. The number of students who completed the pre-cycle was 6 people with a percentage of 21%, cycle I was 11 people with a percentage of 39% and those who had not completed were 17 with a percentage of 61% while in cycle II students who completed were 24 students with a percentage of 86% and those who had not completed were 4 with a percentage of 14%. By looking at the average value obtained, it is hoped that learning about writing advertising texts can be improved again so that it can provide maximum results.